Sports talent identification in weightlifting: test validation - Rojas Quirós, Jimmy Fernando (2013)
The purpose of the study was to validate a modification to the 2 kg medicine ball throw test, which facilitates the search for talented school- age children for Olympic weightlifting. The explosive strength was assessed through a technical movement similar to the weightlifting snatch. 65 children participated, 47.7% male and 52.3% female, the average age was 10.88 ± 0.72 years. After a warm up, the modified 2 kg medicine ball throw test was conducted and in the same work session a previously validated 2 kg medicine ball throw test was performed too. This was done to validate the modified test. To finish the process the modified test was repeated to verify its test-retest reliability. The Pearson correlation analysis was performed to validate and determine validity and reliability of both the test and re-test.  The SPSS version 18.0 was used with a significance level of 0.05. The correlation between the Modified Test and the validated 2 kg medicine ball throw test  was r = 0.533, p <0.001, in the analysis of test - retest, the correlation was r = 0.454, p = 0.007. Therefore, there is a moderate direct correlation between the test and the validated 2 kg medicine ball throw test. The analysis shows this test is valid and reliable, and meets the characteristics of validity and reliability for both sexes in the analysis by gender.